Analysis of the Structure and Classification of Airless Tires - Akbarov Saydullo Askarjon; Abdubannaeva Muslima Komiljon Qizi; Melibayev Makhmujon (Genius Journals, 2022)
Information about the prospects for the use of airless tires in the field of mechanical engineering, as well as in all areas, is covered in the media and literature with a detailed analysis of its design, manufacturing processes and structural dimensions.
Keywords: Car; airless tire; rubber; tubeless